Distress as a mediator for pain and activities of daily living in older adults with fibromyalgia - Gower, Caitlin; Trevitt, Jennifer; Cherry, Barbara J.; Zettel-Watson, Laura (Frontiers in Medicine, 2022)
Introduction Pain, distress, and activities of daily living impact the lives of those with chronic pain. This study investigated distress (depressive symptoms, anxiety) on the relationship between pain (intensity and pain interference) and activities of daily living in individuals with fibromyalgia while controlling for age. Methods The current cross-sectional investigation focused on data from 123 men and women with fibromyalgia. Pain intensity, pain interference and anxiety were measured on 0-10 Likert type scales from the National Fibromyalgia Assessment Questionnaire. Depressive symptoms were assessed using the Beck Depression Inventory II. Activities of daily living (basic, instrumental) were measured with the Physical Activity Inventory Scale. Results It was hypothesized that the relationships between pain intensity and pain interference and activities of daily living in individuals with fibromyalgia would be mediated by the construct of distress while controlling for age. Mediation significantly occurred in both models as predicted. However, those who were older reported lower levels of pain intensity and distress than their younger counterparts, which may be related to time since diagnosis or other factors. Discussion Results of this study suggest that individuals with chronic pain conditions would benefit from treatment options which address distress, specifically depressive symptoms and anxiety.